Comparison of the Watson formula and bioimpedance spectroscopy for measuring body volume and calculating kt/V in patients with peritoneal dialysis - Sixiu Liu; Yuan Feng; Qingyan Zhang; Jian Lu; Nan Li; Ying Liu; Chunming Jiang (Renal Failure)
Background Ascertaining the total body water (V), usually obtained by the Watson formula or bioimpedance spectroscopy (BIS), is crucial for the calculation of Kt/V in patients with peritoneal dialysis (PD). The aim of our study was to compare two different methods of determining V and explore which one is suitable for clinical application.Methods This was a retrospective observational study. V was determined using the Watson formula (Vwat) and BIS (Vbis). The differences between Vbis and Vwat and between Kt/Vbis and Kt/Vwat were assessed. The patients were allocated to different groups according to the Kt/Vwat and Kt/Vbis values. Clinical parameters were compared between these groups to investigate which method of obtaining the Kt/V value was more suitable.Results 150 patients on PD were included. Vwat was significantly higher than Vbis, apart from in female patients with volume overload. Consequently, weekly Kt/Vwat was lower than Kt/Vbis in these patients. A significant negative correlation between mean Vwat-Vbis and overhydration values was also found. Moreover, through uniform manifold approximation and projection analysis, a clustering tendency between patients in the adequate group with both Kt/Vwat and Kt/Vbis > =1.7 and patients in the inconsistent group with Kt/Vwat <1.7 and Kt/Vbis > =1.7 was identified, suggesting that their clinical features were similar.Conclusion There were significant differences between Vwat and Vbis and between Kt/Vwat and Kt/Vbis. Kt/Vwat may underestimate small-solute dialysis adequacy in most cases. Kt/Vbis instead of Kt/Vwat could be accounted for in creating individualized dialysis prescriptions if the patient has no obvious clinical symptoms.